PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK SEKOLAH DASAR - Febrianti azzahra; Muhisom; Siti Nurjanah; Frida Destini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem in this study was the low problem-solving ability in Pancasila Education among fifth-grade students at SD Negeri 2 Way Serdang. This study aimed to determine the effect of the Problem Based Learning model on students’ problem-solving abilities. The research method used was a quasi-experimental design with a non-equivalent control group design. The population of the study consisted of all fifth-grade students at SD Negeri 2 Way Serdang, totaling 52 students. The sample of this study was the students of classes V B and V C at SD Negeri 2 Way Serdang, totaling 36 students. The sample was determined using a purposive sampling technique. Data collection techniques were carried out through tests and non-tests, while data analysis used a simple linear regression test. The results of this study showed that there was an effect of the Problem Based Learning model on the Pancasila Education problem-solving abilities of fifth-grade students at SD Negeri 2 Way Serdang in the 2025/2026 academic year, and there was a difference in problem-solving abilities between students who used the Problem Based Learning model and those who used the Inquiry Based Learning model in fifth grade at SD Negeri 2 Way Serdang in the 2025/2026 academic year.